Design of Non- Engineered Earthquake Resistant Housing in West Sumatera - Fitria, Winda; Guspari, Oni; Afriyani, Sicilia; Putra, Roni Tri; Misriani, Merley (Program Studi Sarjana Teknik Sipil Universitas Internasional Batam, 2024)
This research focuses on the design of earthquake-resistant houses in West Sumatra Province to improve the structural quality of residential buildings. Significant damage to houses caused by previous earthquakes poses a serious threat, especially as it can hinder evacuation processes during disasters. Ensuring individual safety is a top priority in evacuation efforts, making it crucial to build earthquake-safe homes, whether through new construction or renovation, to minimize the risk of casualties. The study employs a quantitative approach guided by the earthquake-resistant house requirements handbook developed by JICA and the Ministry of Public Works. The result is an alternative DED design for a Type 45 house suitable for West Sumatra. This single-story house is designed on hard soil with a structure that meets earthquake standards. The analysis results show the structural specifications as follows: the foundation uses stone with a bottom dimension of 80 cm, a top dimension of 40 cm, and a height of 80 cm; BS beams measure 15 cm x 30 cm; RB beams 15 cm x 20 cm; and columns 20 cm x 20 cm. The average Safety Factor (SF) values are BS beams 1.04, RB beams 1.3, columns > 3, and stone foundation 3, indicating that the planned sections meet the requirements for earthquake-resistant houses. This study aims to contribute to disaster risk mitigation and serve as a guide for communities in constructing earthquake-resistant homes, especially in the West Sumatra region.